El yacimiento arqueológico de Castulo - García-Gelabert, M. Paz (Antigüedad y Cristianismo, 1991)
The author has divided her study in two parts. In the first she makes a brief review of the history of the ibero - roman city Castulo from the beginnin gofits decHne in the third century up to the period when, under the Visigothy domination, it becomes the Episcopal See. In the se cond part of the study the author describes the stratigraphy of the arqueological site of Castulo , excavated by the Profesor J . M . Blázquez in uninterrupted campaigns between los years 1969 and 1983. These campaigns brought to light the following cultural sequences: Bronze Phase; Oretan a Phase; Punic Phase; Roman Phase.